Analysis of the Geographical Features of the Zhytomyr Forest, Its Natural Resources and the Potential for the Development of Tourism - Шевчук, Лариса Миколаївна; Герасимчук, Олена Леонтіївна; Васільєва, Людмила Анатоліївна (Київський національний університет імені Тараса Шевченка, 2023)
The purpose of the study is to substantiate the key elements of the tourism development potential in Zhytomyr Polis, based on the analysis of geographical characteristics and available natural resources of the region. Research methodology. Geographical analysis for the study of geographical location, relief, climate and other natural characteristics of Zhytomyr Polissia. A cartographic method for the purpose of using maps to analyze the distribution of natural resources, tourist facilities and infrastructure. Statistical analysis for the processing and interpretation of statistical data related to tourism in the region, including the number of tourists, tourism revenues, etc. The results. It was determined that the natural resource base of the region is important for recreational activities, taking into account the favorable climatic conditions, water, forest resources and diversity of flora and fauna. The relief of Zhytomyr Polissia contributes to the diversity of climate and biotic resources, which is significant for the development of sports, health and active types of tourism. For the further development of tourism in the region, it is necessary to focus on improving the infrastructure, improving the advertising strategy, creating tourist brands, developing interactive maps and routes, as well as actively attracting the attention of the media to tourist events and projects in the region. Scientific novelty. The scientific novelty of this study consists in a comprehensive analysis of the geographical features of Zhytomyr Polissia, its natural resources and potential for tourism development, which includes an integrated approach to the study of various aspects of the region's tourist attraction. The study offers a new perspective on the possibilities of using natural resources, geographical location and historical and cultural heritage of Zhytomyr Region in the context of tourism development. Practical significance. The article is of practical importance in determining the prospects and ways of development of the tourism and recreation sphere in Zhytomyr Polis. It points to the possibilities of using geographical location, natural and cultural resources to stimulate both domestic and international tourism. The aspects highlighted in the article can be used to plan and implement tourism projects, which will contribute to the economic development of the region. The results of the study can be used by local authorities, tourism organizations and investors to develop effective tourism development strategies, create new tourism products and improve existing ones.

Мета. Метою статті є аналіз рекреаційного потенціалу Черкаської області, характеристика діяльності закладів, які спеціалізуються на лікувально-оздоровчому туризмі, визначення їх просторової структури. Методика. Для дослідження були використані загальнонаукові методи, а саме аналіз, синтез та узагальнення. Джерелами інформації для дослідження є наукові праці фахівців, дослідження яких стосуються лікувально-оздоровчого туризму, а також дані щодо рекреаційних закладів Черкаської області, розміщені у мережі інтернет. Результати. Встановлено передумови розвитку та природно-лікувальні фактори, що лежать в основі роботи закладів рекреації Черкащини. Лікувально-оздоровчі заклади Черкащини представлені переважно санаторіями, санаторіями-профілакторіями та базами відпочинку. З’ясовано, що санаторно-курортні та оздоровчі заклади розміщуються на території області нерівномірно та сконцентровані переважно біля узбережжя Кременчуцького водосховища. Досліджено існуючу матеріально-технічну базу лікувально оздоровчих закладів Черкаської області та розширено уявлення про їх спектр послуг. Наукова новизна. Проаналізовано діяльність найбільш відомих лікувально-оздоровчих закладів Черкаської області. З’ясовано просторову структуру та виявлено основні фізико-хімічні та лікувальні властивості мінеральних вод, які використовуються закладами рекреації для лікування та профілактики різноманітних захворювань. Надано пропозиції щодо розширення асортименту послуг закладів. Практична значимість. Результати досліджень, висвітлені у статті, можуть бути використані працівниками закладів рекреації Черкащини та інших лікувально-оздоровчих комплексів України, а також в рамках освітнього процесу здобувачами освіти спеціальностей 242 «Туризм», 014.07 «Середня освіта (Географія)» та інших з метою розширення уявлення про ресурсний та рекреаційний потенціал Черкаської області.
Аналіз географічних особливостей Житомирського Полісся, його природних ресурсів та потенціалу для розвитку туризму
Keywords: Житомирське Полісся; географічне положення регіону; туристичний потенціал; кліматичні умови; стратегія розвитку туризму; туристичні послуги; Zhytomyr Polissia; geographical location of the region; tourist potential; climatic conditions; tourism development strategy; tourist services